Kolaborasi Marketing Public Relation (MPR) dan Corporate Social Responsibillity (CSR) dalam membangun citra positif dan loyalitas nasabah pada perbankan syariah - Wahyudi, Muhammad Arifky (Maliki Interdisciplinary Journal, 2024)
Islamic banking in Indonesia has experienced significant development, reflected in the growing public interest in products and services that comply with Islamic principles. This article discusses the roles of Marketing Public Relations (MPR) and Corporate Social Responsibility (CSR) in building a positive image and customer loyalty in the Islamic banking sector. MPR serves to enhance public understanding of products and services, while CSR contributes to fostering good relationships with the community through sustainable social programs. This study analyzes the implementation of MPR strategies at PT. BPRS Sarana Prima Mandiri and Bank Syariah Indonesia (BSI), demonstrating that an integrated approach between MPR and CSR can enhance reputation and customer trust. The findings indicate that effective strategies in MPR and CSR not only improve the company’s image but also contribute to the growth of customer numbers and their loyalty.